Sociodemographic characterization of Cassava farmers in Cameroon - Claudette, Dickmi Vaillam; Roger, Tchouamo Isaac (Journal of Scientific Agriculture, 2022)
The aim of this study was to profile Cameroonian cassava farmers in the Adamawa, Centre, East and South regions of Cameroon. Four (04) quantitative and ten (10) qualitative variables were analyzed using correlation analysis and Chi-square-based association testing (alpha=0.05) respectively. The results suggest that cassava farming is practiced more by women than by men. Also, the average age of cassava farmers across regions is 42.2 years. Some of Cameroon’s cassava farmers own farmland, and few have fields that are specifically devoted to Cassava cultivation due to the practice of mixed cropping and crop rotation. Moreover, the majority of Cameroonian cassava farmers consume the cassava they grow and process, and most of them are well-educated, being able to read and write, with 51% of women involved. Smartphone use is very widespread among Cassava farmers in the Centre and South regions, where the proportions between the two sexes are 26.1% (men) versus 30.3% (women), and 30.9% (men) versus 29.4% (women) respectively. The same applies to internet access. Farmers in Adamawa and the East have little access to the internet. Furthermore, very few cassava farmers belong to farmers’ organizations, and they use the income from selling the cassava they produce and process to ensure their household’s food and health security, and to send their children to school. Finally, participation in community activities is not widespread in Adamawa and the South and over the last five years, very few cassava farmers have acquired assets from the sale of cassava.